A snapshot of nephron-sparing surgery in Italy: A prospective, multicenter report on clinical and perioperative outcomes (the RECORd 1 project). Issue 3 (March 2015) - Schiavina, R.; Mari, A.; Antonelli, A.; Bertolo, R.; Bianchi, G.; Borghesi, M.; Brunocilla, E.; Fiori, C.; Longo, N.; Martorana, G.; Mirone, V.; Morgia, G.; et al.
Abstract Introduction Nephron-sparing surgery (NSS) has become the standard of care for the surgical management of small and clinically localized renal cell carcinoma (RCC). The conservative management of those RCCs is increasing over time. Aim of this study was to report a snapshot of the clinical, perioperative and oncological results after NSS for RCC in Italy. Material and methods We evaluated all patients who underwent conservative surgical treatment for renal tumours between January 2009 and December 2012 at 19 urological Italian Centers (RECORd project). Perioperative, radiological and histopathological data were recorded. Surgical eras (2009 vs 2012 and year periods 2009–2010 vs 2011–2012) were compared. Results Globally, 983 patients were evaluated. More recently, patients undergoing NSS were found to be significantly younger (p = 0.05) than those surgically treated in the first study period, with a significantly higher rate of NSS with relative and imperative indication (p < 0.001). More recently, a higher percentage of procedures for cT1b or cT2 renal tumours was observed (p = 0.02). Utilization rate of open partial nephrectomy (OPN) constantly decreased during years, laparoscopic partial nephrectomy (LPN) remained almost constant while robot-assisted partial nephrectomy (RAPN) increased. The rate of clampless NSS constantly increased over time. The use of at least one haemostatic agent has been significantly more adopted in the most recent surgical era (p < 0.001). Conclusions The utilization rate of NSS in Italy is increasing, even in elective and more complex cases. RAPN has been progressively adopted, as well as the intraoperative utilization of haemostatic agents and the rate of clampless procedures.